A reservoir-source study for the Zubair formation in the northern Rumaila field, south of the Mesopotamian Basin, southern Iraq - Hadeer Abdul Muttalib Al-Aradi/ Fahad Mansour Al-Najm / Amer Jassim Al-Khafaji3 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The main purpose of the research is to study and evaluate the formation of Zubair in the northern Rumaila field from the two sides of the reservoir (the main Pay reservoir (the upper sand member) and the source (the upper shale member). The results obtained from the study indicated that the petrophysical properties improve towards the south of the field, as the porosity, permeability and hydrocarbon saturation increase while they decrease towards the north of the field. It was also noted that the water saturation increased towards the west of the field. As for the source study, the results showed that the Zubair formation contained a good amount of organic matter generating hydrocarbons and entering the stage of peak maturity, in addition to a good potential for the source rocks to generate hydrocarbons